Historis Studi Islam Anak Madrasah Ibtidaiyah - Andi Setiyawan; Fu`ad Arif Noor (Pascasarjana IAIN Sultan Amai Gorontalo, 2021)
Islam is a complex and all-embracing religion. The treatise of Islam is not based solely on aqidah, but much larger than that. It is not an easy matter to introduce and teach Islamic studies to students particularly they still are on the Madrasah Ibtidaiyah. For the children of Madrasah Ibtidaiyah to present and understand Islamic studies, approaches to study are necessary for them to understand it easier. The research used philosophical, sociological, theological, anthropological and historical approaches as the steps to introduce Islam to students. However, in this research, the researcher discussed how to introduce Islam to the students of Madrasah Ibtidaiyah using a historical approach. The research method used was a literature study research method, which was a study of the literature. The method for collecting data is a review of books, notes, and reports on literature relating to the history of Islamic studies of the children of Madrasah ibtidaiyah. According to the findings of this study, it is possible to introduce and teach the cultivation of Islamic principles to Madrasah Ibtidaiyah students using a historical approach